Conjugation of Daunorubicin to Monoclonal Antihuman Sarcoma Antibody by a Novel Method - Michel Pagé; Denis Thibeault; Hélène Tremblay; Christiane Noël; Marie-Josée Perron (Canadian Journal of Infectious Diseases)
Most of the reported methods for coupling anthracycline drugs to antibody result in either a loss of pharmacological activity or yield antibodies which have lost much of their immunological specificity. The use of glutaraldehyde for coupling saves both the pharmacological and immunological activities but it causes some polymerization of the antibody or of the macromolecular carrier which is undesirable for in vivo use. A new coupling procedure is reported which uses an activated derivative of daunorubicin added to monoclonal antihuman sarcoma antibody. This coupling procedure has not resulted in significant polymerization of the antibody or Joss of pharmacological activity determined by testing normal and tumour cell Lines in vitro.